PEMAHAMAN KADER POSYANDU TENTANG PENANGANAN PENYAKIT DEMAM BERDARAH DI PUSKESMAS TLOGOSARI KULON SEMARANG - Susi Nurhayati; Retno Apriliyanti (Universitas Muhammadiyah Semarang, 2015)
Dengue Fever is the transmitted diseases that is caused by Dengue Virus, it is speared by Aedes Aegypty that is signed by immediately fever for 2-7 days without unclear symptoms. The symptoms of Dengue Fever are weak, anxious, painful abdomen, bleeding under the skin(petechiae), echymosis. In Central Java, there were 4.121 cases and found 182 deaths. In Semarang especially Tlogosari Kulon District, in 2014, this cases reached 101 cases and from January – February 201, there are 20 cases. So, it is a serious problem and Semarang is included in Endemic Zone of Dengue Fever. This Research was aimed to increase the understanding of Health Practitioners dealing with the Dengue Fever handling Management at Tlogosari Kulon Health District Centre Semarang. This research used quantitative design with quasy experiment with one group experiment, data analyis used univariate, bivariate with Paired t-test. The sampling technique used total sampling as many as 50 respondents. The result showed there is a significant difference of Dengue Fever understanding before and after the intervension with p value (0,000) or equivalent with 1,178. It is expected that health practisioners must apply the early prevention of Dengue Fever in their environment.Keywords: Dengue Fever, Health Practisioners, Health Education